(untitled) (Journal on studies and research of academic knowledge, 2022)
The Business Continuity Plan (BCP) is the set of activities planned in a given an organization, to be able to respond to incidents that may impact people, operations and the ability to deliver goods and services to the market. This Plan becomes particularly important for a NIC entity, administrator and sponsor of a country’s top-level Internet domain. This work focuses on the proposal of a BCP for the NIC-PY harmonizing the criteria suggested by ICANN and COBIT 2019. The result is a grid of tasks to include in the BCP of the NIC-PY for immediate start-up.